Efficacy of non‐invasive respiratory support modes for primary respiratory support in preterm neonates with Respiratory Distress Syndrome: Systematic review and network meta‐analysis - Ramaswamy, VV; More, K; Roehr, CC; Bandiya, P; Nangia, S (Wiley, 2020)
Objectives To compare the efficacy of different noninvasive respiratory support (NRS) modes for primary respiratory support of preterm infants with respiratory distress syndrome (RDS). Design Systematic review and network meta‐analysis using the Bayesian random‐effects approach. MEDLINE, EMBASE, and CENTRAL were searched. Interventions High flow nasal cannula (HFNC), continuous positive airway pressure (CPAP), bilevel CPAP (BiPAP), noninvasive positive pressure ventilation (NIPPV). Main Outcome Measures Requirement of invasive mechanical ventilation (MV), any treatment failure. Results A total of 35 studies including 4078 neonates were included. NIPPV was more effective in decreasing the requirement of MV than CPAP (risk ratios [95% credible interval]: 0.60 [0.44, 0.77]) and HFNC [0.66 (0.43, 0.97)]. Surface under the cumulative ranking curve (SUCRA) for NIPPV, BiPAP, HFNC, and CPAP were 0.95, 0.59, 0.32, and 0.13. For the outcome of treatment failure, both NIPPV and BiPAP were more efficacious compared to CPAP and HFNC (0.56 [0.44, 0.71] NIPPV vs CPAP, 0.69 [0.51, 0.93] BiPAP vs CPAP, 0.42 [0.30, 0.63] NIPPV vs HFNC, 0.53 [0.35, 0.81] BiPAP vs HFNC). The SUCRA for NIPPV, BiPAP, CPAP, and HFNC were 0.96, 0.70, 0.32, and 0.01. NIPPV was associated with a reduced risk of air leak compared to BiPAP and CPAP (0.36 [0.16, 0.73]; 0.54 [0.30, 0.87], respectively). NIPPV resulted in lesser incidence of bronchopulmonary dysplasia or mortality when compared to CPAP (0.74 [0.52, 0.98]). Nasal injury was lesser with HFNC compared to CPAP (0.15 [0.01, 0.60]). Conclusions Most effective primary mode of NRS in preterm neonates with RDS was NIPPV.